2017
DOI: 10.23910/ijbsm/2017.8.6.3c0156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage and Weed Control Methods in Maize (Zea mays) -Wheat (Triticum aestivum) Cropping System

Abstract: An experiment was conducted to find out the effect of tillage and weed control methods on weed dynamics and productivity of maize (Zea mays L.)-wheat (Triticum aestivum L.) cropping system. The treatments comprised of combinations of tillage sequences in main plots and weed control methods in sub plots. The results revealed that zero tillage in rainy and winter season is as good as conventional tillage method in reducing weed dry matter and producing maize and system yield, while, conventional tillage in rainy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In general, there was progressive increase in dry weight of weeds with time and lesser weed dry matter was recorded in conventional tillage (CT), followed by minimum tillage (MT) and zero tillage (ZT) practice at all the stages. Upasani et al (2017) also reported non-significant effect of tillage methods in maize -wheat system on dry-matter accumulation of weeds. The total dry-matter of weeds in maize crop was higher in ZT plots than MT and CT practices (Kumar and Angadi, 2014).…”
Section: Weed Dry Matter and Weed-control Efficiencymentioning
confidence: 98%
“…In general, there was progressive increase in dry weight of weeds with time and lesser weed dry matter was recorded in conventional tillage (CT), followed by minimum tillage (MT) and zero tillage (ZT) practice at all the stages. Upasani et al (2017) also reported non-significant effect of tillage methods in maize -wheat system on dry-matter accumulation of weeds. The total dry-matter of weeds in maize crop was higher in ZT plots than MT and CT practices (Kumar and Angadi, 2014).…”
Section: Weed Dry Matter and Weed-control Efficiencymentioning
confidence: 98%
“…Therefore, application of one or more herbicides as pre-emergence or post emergence or combination of both, will help to control divergent weed flora like sedges, grasses and broad leaf weeds in maize without causing long term adverse effects. Sole application of atrazine which is a widely used herbicide does not provide effective control of weeds (Upasani et al, 2017). Mixing of herbicides for better control of weeds is emerging to tackle the sturdy weed population.…”
Section: Effect Of Ready MIX Application Of Herbicide On Weed Dynamic...mentioning
confidence: 99%
“…No-tillage is the practice of sowing crops directly in the residues of the previous crop without cultivation, while stubbles are retained and weeds are controlled with herbicide (Labios et al, 2002). Zero tillage would reduce the soil erosion and loss of soil organic matter (Lal, 2004, Chalise et al, 2020 and increase yield (Upasani et al, 2017). Khan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%